Profil Kemampuan Literasi Siswa Sekolah Dasar Kelas Tinggi di Lewa Paku - Iona Lisa Ndakularak; Stevvileny Angu Bima; Erwin Randjawali; Mayun Erawati Nggaba; Djemi Djami Ishak; Yeni Rinawati (Jurnal Sekolah Dasar, 2023)
This study aims to describe the literacy ability profile of high school elementary school students in Malumbi, East Sumba Regency. This literacy ability was carried out in one of the 5th grade students' schools in the high class area as a reference point used to analyze comparisons before finally moving on to a larger stage of research scope. This type of research is qualitative with the instrument used in collecting the data is the literacy test, namely the test uses EGRA (Early Grade Reading Assessment) measurements, interviews and observations. The results of the research on the school's numeracy skills which were collected through a literacy test found that elementary school students were in the very low category with an average score of 42.67. This is caused by several factors such as the lack of textbooks which so far have only been provided while at school, difficulties in teacher delivery because students are more familiar with using their mother tongue, there are no modules that are easy to understand in the context of local wisdom which supports students to be able to study at home, and students are not used to reading story problems and then draw conclusions from the story, so that reading literacy skills in this test recognize the sound of letters, read words, read meaningless words, fluency in oral reading in context, reading comprehension, listening comprehension, dictation.